2021
DOI: 10.3390/nano11102523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Concentration on the Electrochemical Properties of Cobalt Ferrite Nanocomposite Materials

Abstract: A two-step process was applied to synthesize the cobalt ferrite-graphene composite materials in a one-pot hydrothermal reaction process. Graphene Oxide (GO) was synthesized by a modified Hummer’s method. The synthesized composite materials were characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR). The XRD and FTIR results were in good agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The poor corrosion stability of a nanocomposite cobalt ferrite/graphene was attributed to its high electronic conductivity [82,83]. Insufficient stability of many redox-active materials potentially of interest for application in supercapacitor electrodes in contact with acidic electrolyte solutions has been noticed [84].…”
Section: Observationsmentioning
confidence: 99%
“…The poor corrosion stability of a nanocomposite cobalt ferrite/graphene was attributed to its high electronic conductivity [82,83]. Insufficient stability of many redox-active materials potentially of interest for application in supercapacitor electrodes in contact with acidic electrolyte solutions has been noticed [84].…”
Section: Observationsmentioning
confidence: 99%
“…It is reported that dosage amount of cobalt aluminium ferritegraphene oxide-titania ferrite system increased the physical and chemical structural properties [8,9]. Spinal ferrite (Co 2+ x Fe 2+ 1-x)-(Al 3+ y Fe 3+ 2-y)O4 have attracted interest to many applications, substitution of Fe 3+ ions with Al 3+ ions in +III oxidation state [10] and Fe 2+ ions with Co 2+ ions in +II oxidation state [11], the ferrite…”
Section: Introductionmentioning
confidence: 99%
“…These promising structural, electrical, optical, magnetic, mechanical, and thermal properties of graphene have opened new avenues for learning materials science. 5,6 Compared with other nanomaterials, so ferrites are less expensive, reliably stable, and easy to prepare. Their high permeability at radio frequencies, high Curie temperature, high electrical resistivity, low eddy current loss, ne environmental stability, and mechanical hardness make them suitable for application in many devices, such as microwave apparatus, inductors, choke coils, transformers, and electromagnetic interface (EMI) suppressors.…”
Section: Introductionmentioning
confidence: 99%